Photon-counting CT review. (November 2020) - Flohr, Thomas; Petersilka, Martin; Henning, Andre; Ulzheimer, Stefan; Ferda, Jiri; Schmidt, Bernhard
Highlights: Photon-counting detectors are a promising new technology for computed tomography (CT) systems. They provide energy-resolved CT data at high spatial resolution without electronic noise and with improved tissue contrasts. Pre-clinical whole-body photon-counting CT prototypes are currently used for pre-clinical testing in human subjects. Abstract: Photon-counting detectors are a promising new technology for computed tomography (CT) systems. They provide energy-resolved CT data at very high spatial resolution without electronic noise and with improved tissue contrasts. This review article gives an overview of the principles of photon-counting detector CT, of potential clinical benefits and limitations, and of the experience gained so far in pre-clinical installations.